2007
DOI: 10.3989/cyv.2007.v46.i6.214
|View full text |Cite
|
Sign up to set email alerts
|

Estudio por difracción de rayos X de la hidratación de mezclas de CaAl<sub>2</sub>O<sub>4</sub> - Humo de silice

Abstract: Se ha estudiado la influencia del humo de sílice sobre el mecanismo de hidratación del monoaluminato de calcio (CaAl 2 O 4 ) a temperatura ambiente y con una relación agua/sólidos de 0,5. La evolución de las fases hidratadas, que se forman en los primeros instantes de la reacción, se ha estudiado por difracción de rayos X de laboratorio con una resolución temporal de 36 min. In situ X-ray difraction study of hidration of CaAl 2 O 4 -amorphous silica mixturesThe influence of the amorphous silica on the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The formation of various short-lived crystalline phases along the dehydration process like Ca 12 Al 14−y Si y O 32 (O,OH) 1+y/2 , Ca(OH) 2 and CaO were observed. The mean (linear) thermal expansion coefficients for the hydrogarnet and katoite are calculated in the temperature range 25-250 • C.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The formation of various short-lived crystalline phases along the dehydration process like Ca 12 Al 14−y Si y O 32 (O,OH) 1+y/2 , Ca(OH) 2 and CaO were observed. The mean (linear) thermal expansion coefficients for the hydrogarnet and katoite are calculated in the temperature range 25-250 • C.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3] The main role of silica fume is improving the rheology of the refractory concrete mix for better pumping and stability. Silica fume is widely used in LCCs and when combined with admixtures a system with low water demand can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the XRD findings for the 16-h CAC pastes showed that the hexagonal hydrate content (CAH 10 and C 2 AH 8 ) was higher in the admixture-free paste than in the paste containing PC1 (see Figure and Table ) . The FTIR results for these same pastes confirmed the higher degree of paste hydration in the absence of the admixture, with more intense vibration bands (in the 3650–3400 and 1020 cm –1 regions) associated with monocalcium aluminate hydration products.…”
Section: Discussionmentioning
confidence: 78%